2008
DOI: 10.1097/psy.0b013e318177216c
|View full text |Cite
|
Sign up to set email alerts
|

Do Positive Psychosocial Factors Predict Disease Progression in HIV-1? A Review of the Evidence

Abstract: Adding to a traditional stress perspective, behavioral medicine has been focusing increasingly on investigating the potential impact of positive psychosocial factors on disease course in HIV. Dispositional optimism, active coping, and spirituality show the most evidence for predicting slower disease progression, although the data are not entirely consistent. Findings for the role of social support are mixed, although indications are that it may be particularly helpful at later stages of illness. Many of the ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
104
1
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(112 citation statements)
references
References 102 publications
2
104
1
5
Order By: Relevance
“…Park 2004;Prati and Pietrantoni 2009). Although no studies on the Big Five and PTG among PLWH have been conducted, several authors have proved the importance of extraversion in maintaining good overall and HIV-specific quality of life, slower disease progression, as well as satisfactory social relationships, despite HIV-related stigma (Ironson and Hayward 2008;Kumar 2015;Penedo et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Park 2004;Prati and Pietrantoni 2009). Although no studies on the Big Five and PTG among PLWH have been conducted, several authors have proved the importance of extraversion in maintaining good overall and HIV-specific quality of life, slower disease progression, as well as satisfactory social relationships, despite HIV-related stigma (Ironson and Hayward 2008;Kumar 2015;Penedo et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Wilson et al (2016), in a national study of HIV-infected women, observed that positive affect predicted viral suppression, which may also be understood that viral suppression can affect positive affect and generate a cycle of improvement for PLWH. Moreover, positive affect among PLWH was negatively related to the level of depression (Li, Mo, Wu, & Lau, 2016) and slower HIV progression (Ironson & Hayward, 2008), and this effect was independent of negative affect. Employing Fredrickson’s (2001) broaden-and-build theory – in which positive emotions my enhance personal resources, well-being and psychological growth over time – Yu et al (2014) claimed that positive affect should be treated as one of the most important predictors of PTG, especially in cases of life threatening diseases.…”
Section: Discussionmentioning
confidence: 99%
“…HIV-related distress impacts PLWH’s well-being and physical health (e.g. Chida & Vedhara, 2009; Ickovics et al, 2006; Leserman, 2008), very little is known about the role of positive emotions in various aspects of functioning among this patient group, making this topic a candidate for further investigation (Ironson & Hayward, 2008; Moskowitz et al, 2017). …”
mentioning
confidence: 99%
“…• Optimistic individuals report faster recovery and better quality of life after significant cardiac interventions such as coronary artery bypass surgery or disorders such as myocardial infarction 21,22 • Optimism is inversely related to perceived levels of distress and rapid disease progression and is www.ccnonline.org directly correlated with improved survival rates in persons with HIV, 23 in some forms of cancer, [24][25][26] in college students adapting to their initial semester, 27 in pregnant women, 28 and in elderly people.…”
Section: Psychological Health Benefits Of Gratitudementioning
confidence: 99%